A TEN-YEAR ANALYSIS OF ANTIHYPERTENSIVE THERAPY IN OVER-EIGHTY-YEARS-OLD-PATIENTS. (June 2018) - A.Grossi,; Cattaneo, E.; Tandurella, N.; Moretti, S.; Cavallaro, G.; Test, L. Robustelli; Agostinis, M.; Pierobon, V.; Tavecchia, L.; Mancuso, V.; Mongiardi, C.; Montalbetti, L.; et al.
Abstract : Objective: To investigate type and number of antihypertensive drugs in over-eighty-years-old-patients and five years follow-up changes in antihypertensive therapy. To evaluate also prevalence of adequate blood pressure (BP) control, orthostatic hypotension, cardiovascular (CV) risk factors and comorbidities in this population. Design and method: From 2007 to 2015 we enrolled 239 over-eighty-years-old-hypertensives (systolic-BP > 140mmHg and/or diastolic-BP > 90mmHg and/or use of antihypertensive-drugs). For each patient we assessed home and office-BP, other CV-risk factors, organ damage (left ventrcular hypertrophy-LVH, microalbuminuria, intima-media thickening), comorbidities, antihypertensive-drugs. Follow-up consisted in telephone-interview (July/2017) to detect if patients were alive, had CV-events and/or changed their antihypertensive-therapy. Results: At the first visit, BP-values were controlled (<140/90mmHg) in 133 patients (55.6%). Systolic-BP was > 140mmHg in 87 patients (36.4%), diastolic-BP > 90mmHg in 3 (1.3%), whereas both systolic and diastolic-BP were uncontrolled in 16 (6.7%). Orthostatic hypotension was diagnosed in 19.2% patients. 133 patients had LVH (77.3%) and 107 carotid-plaques (70.9%). Among CV-risk factors, heart diseases affected 70 patients (heart failure-6.7%, coronary diseases-10%, atrial fibrillation-12%), cerebrovascular-diseases interested 14 patients (5.8%), chronic kidney failure affected 46 patients (19.2%), diabetes and/or dyslipidemia were found in 134 patients (56.1%). 52.3% of patients took 2–3 type of antihypertensive drugs, 32.7% 4 or more, 12.6% followed monotherapy, 2.5% didn't take antihypertensive molecules. Generally, well-controlled hypertensives used less drugs than uncontrolled ones (2.75 ± 1.4vs3.23 ± 1.35, p:0.008). Most used drugs were: Calcium-antagonists (CA, 66%), Angiotensin-receptor-blockers (ARB, 57%), Beta-blockers (BB, 42%), thiazide-diuretics (TD, 47%), Angiotensin-converting-enzyme-inhibitors (ACE-I, 33%), sympatholytic (25%), loop-diuretics (LD, 15%), mineralcorticoid-antagonists (MA, 6%). After 4.9 ± 2.2 years, 51.7% of patients took 2–3 type of antihypertensive drugs, 25.3% 4 or more, 16.7% followed monotherapy, 6.3% didn't take antihypertensive molecules. Thus, the mean number of drugs passed from 2.96 ± 1.40 to 2.58 ± 1.34, with cut both in male and female and both in well-controlled and uncontrolled hypertensives. We found the rise of LD prescriptions (p:0.004), whereas CA (p:0.04), TD (p:0.001) and ARB (p:0.01) were less used. 28 patients were lost at the follow-up (11.7%), 37 were died (15.5%:54% for CV-events, 46% for other causes). Among the 174 alive-patients (72.8%), 6.9% had CV-events. Conclusions: Our data underlined deprescribing of hypertensives-drugs in an out-patient population of over-eighty-year-old-hypertensives, especially for TD, ARB and CA.